Formal Modeling and Analysis of Timed Systems 9th International Conference, FORMATS 2011, Aalborg, Denmark, September 21-23, 2011, Proceedings - Fahrenberg, Uli; Tripakis, Stavros (Theoretical Computer Science and General Issues, 2011)
This book constitutes the refereed proceedings of the 9th International Conference on Formal Modeling and Analysis of Timed Systems, FORMATS 2011, held in Aalborg, Denmark, in September 2011. The 20 revised full papers presented together with three invited talks were carefully reviewed and selected from 43 submissions. The papers are organized in topical sections on probabilistic methods, robustness, games, verification and testing, verification, hybrid systems, and applications.